تأثير إعادة هندسة العمليات على النجاح الإستراتيجي - دراسة ميدانية بشركة موبيليس وكالة - سوق أهراس - نريمان شواقرية; مريم طبيب (My University, 2022)
This research aims to highlight the impact of process re-engineering on the strategic success of Mobilis, where we dealt in the theoretical side with the basic concepts of process re-engineering in addition to the conceptual framework of innovative thinking. Process re-engineering, as well as change management In the second chapter, we touched upon strategic success in all its theoretical aspects, in addition to its measurement indicators of survival, adaptation, and growth. As for the field study, it was conducted in Mobilis Company - Souk Ahras -. In order to address the subject and test hypotheses, the questionnaire was relied upon, so we were able to understand the aspects of the subject and concluded that the process of re-engineering operations is a radical process, i.e. starting over and not restoration helps the progress of institutions. ................................................ يهدف هذا البحث الى إبراز تأثير إعادة هندسة العمليات على النجاح الإستراتيجي شركة موبيليس، حيث تناولنا في الجانب النظري المفاهيم الأساسية لإعادة هندسة العمليات بالإضافة الى الإطار المفاهيمي للتفكير الإبتكاري ومن ناحية أخرى تعرفتا على التركيز على الزبائن فب إعادة هندسة العمليات إضافة الى التوافق الإستراتيجي والإستثمار التكنولوجي في إعادة هندسة العمليات،إضافة الى إدارة التغيير فيها أما في الفصل الثاني فتطرقنا الى النجاح الإستراتيجي بكل نواحيه النظرية إضافة الى مؤشرات قياسه المتمثلة في البقاء,التكيف،والنمو. أما الدراسة الميدانية أجريت في شركة موبيليس –سوق أهراس- . ولمعالجة الموضوع وإختبار الفرضيات تم الإعتماد على الإستبيان ،فتمكنا من الإحاطة بجوانب الموضوع وإستنتجنا أن عملية إعادة هندسة العمليات هي عملية جذرية أي البدء من جديد وليس الترميم تساعد على تقدم المؤسسات،أما النجاح الإستراتيجي هم جوهر أنتلاق المؤسسات للبحث عن الوضع الملائم للتكيف مع متغيرات البيئة.